Peningkatan Kekuatan Motorik Pada Pasien Stroke Non Hemoragik Dengan Menggenggam Bola Karet : Systematic Review - Ida Rahmawati; Neni Triana; Loren Juksen; Zulfikar Zulfikar (Jurnal Kesehatan Medika Udayana, 2022)
Background: Stroke is a neurological disease that is often found and stroke management must be done quickly and appropriately. Stroke has various impacts, one of which is paralysis of the limbs or disability. Purpose : to analyze articles related to increasing motor strength in non-hemorrhagic stroke patients by gripping a rubber ball. The search strategy used two electronic databases, namely: Pubmed and Google Scholar and following the PRISMA (Preffered Reporting Items for Systematic Review and Meta Analysis) protocol with a publication range of 2012-2019, obtained 10 articles that matched the inclusion and exclusion criteria. Methods: systematic review is used in this research method by searching for article topics based on the database: Pubmed and Google Scholar according to the PRISMA diagram. The diagram includes identification, eligibility, screening, and determination of articles that enter the inclusion criteria. Furthermore, the articles that have been found will be reviewed systematically using the Joana Brigg Institute Check list (JBI). The search for articles for identification began in April-June 2020 with a range of 2012-2019 in each database. The three keywords used in the article search consisted of: motor strength, non-hemorrhagic stroke, gripping a rubber ball. Article searches are also performed by combining words using the AND keyword; OR. Results: the study showed that stroke patients with upper extremity weakness after gripping a rubber ball therapy will experience an increase in muscle strength when they do exercise frequently. Conclusion: rubber ball gripping exercise can be used as a nursing intervention in providing nursing care. Rubber ball gripping exercise is also a rehabilitation program that aims to make non-hemorrhagic stroke sufferers achieve the maximum possible functional ability and prevent complications and recurrent strokes. The exercise program must also be structured and focused on doing more repetitions of exercise 2 times a day for 8 days so that the exercises carried out can achieve the expected results, so that it can lead to an increase in muscle strength properly.